2006
DOI: 10.1186/1477-7525-4-11
|View full text |Cite
|
Sign up to set email alerts
|

Better quality of life with neuropsychological improvement on HAART

Abstract: Background: Successful highly active antiretroviral therapy (HAART) regimens have resulted in substantial improvements in the systemic health of HIV infected persons and increased survival times. Despite increased systemic health, the prevalence of minor HIV-associated cognitive impairment appears to be rising with increased longevity, and it remains to be seen what functional outcomes will result from these improvements. Cognitive impairment can dramatically impact functional ability and day-to-day productivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 33 publications
0
32
0
2
Order By: Relevance
“…Among the 12 included studies, ten showed a positive correlation between adherence and QoL, with a concomitant increase in treatment adherence and QoL. 1,4,7,12,13,16,17,23,24,26 In the three prospective cohort studies, 7,13,27 the success of treatment adherence over time was associated with greater QoL. In the cross-sectional studies, 1,12,17,23,24,26 it was also possible to observe positive correlations between QoL and adherence.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Among the 12 included studies, ten showed a positive correlation between adherence and QoL, with a concomitant increase in treatment adherence and QoL. 1,4,7,12,13,16,17,23,24,26 In the three prospective cohort studies, 7,13,27 the success of treatment adherence over time was associated with greater QoL. In the cross-sectional studies, 1,12,17,23,24,26 it was also possible to observe positive correlations between QoL and adherence.…”
Section: Resultsmentioning
confidence: 98%
“…Despite the positive correlations in the studies, some factors should be considered, such as the use of nonrandomized convenience samples, 1,7,12,16,17,23 sampling of only male patients 23 and utilization of QoL instruments not specifi c to HIV/AIDS patients. 4,12,13,16,26 The relationship between treatment adherence and QoL should be more thoroughly explored. Ideally, these two aspects should occur simultaneously, with adherence improving treatment outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The cART regimen aims towards controlling systemic viremia and inflammation (Gendelman et al , 1998), improving immunological function, and preventing extensive CNS inflammation (Spudich et al , 2011), resulting in increased in life expectancy and decreased HIV-related neurological complications (Parsons et al , 2006). Although cART does not completely eradicate viral-induced neurologic dysfunction, it has proven considerably effective in ameliorating further CNS progression by preventing neuronal death and decreasing CNS viral titers (Gendelman et al , 1998; Xia et al , 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Antiretroviral therapy (ART) extends the lives of persons living with HIV and AIDS and improves the quality of their lives [1,2]. The rapid increase in ART coverage in low- and middle-income countries, especially in Sub-Saharan Africa, has also led to a clear decline in premature mortality [3,4].…”
Section: Introductionmentioning
confidence: 99%